2006
DOI: 10.1002/ejsp.342
|View full text |Cite
|
Sign up to set email alerts
|

Development of the positive–negative asymmetry effect: in‐group exclusion norm as a mediator of children's evaluations on negative attributes

Abstract: (2007) Development of the positive-negative asymmetry effect: In-group exclusion norm as a mediator of children's evaluations on negative attributes. European Journal of Social Psychology, 37 (1). pp. [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] According to social identity theory (SIT: Tajfel & Turner, 1986) intergroup bias is achieved as a result of individual's striving for positive social distinctiveness, in the context of some in-group identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 71 publications
(112 reference statements)
7
41
0
1
Order By: Relevance
“…factor in children's developing ability to control of their explicit ethnic intergroup attitudes Rutland, 2004;Rutland et al, 2005;Rutland, Brown, Cameron, Ahmavaara, Arnold, & Samson, 2007). Research on adults also suggests that they are motivated to control intergroup bias due to specific egalitarian social norms (e.g., Monteith, Deenan, & Tooman, 1996;Dovidio, Kawakami, Johnson, Johnson, & Howard, 1997;Lowery, Hardin, & Sinclair, 2001;Towles-Schwen & Fazio, 2003;Dasgupta & Rivera, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…factor in children's developing ability to control of their explicit ethnic intergroup attitudes Rutland, 2004;Rutland et al, 2005;Rutland, Brown, Cameron, Ahmavaara, Arnold, & Samson, 2007). Research on adults also suggests that they are motivated to control intergroup bias due to specific egalitarian social norms (e.g., Monteith, Deenan, & Tooman, 1996;Dovidio, Kawakami, Johnson, Johnson, & Howard, 1997;Lowery, Hardin, & Sinclair, 2001;Towles-Schwen & Fazio, 2003;Dasgupta & Rivera, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Developmental psychologists have recently begun to demonstrate that group norms affect young children's explicit ethnic intergroup attitudes (Apfelbaum, Pauker, Ambady, Sommers, & Norton, 2008;Rutland, 2004;Rutland et al, 2005;Rutland et al, 2007). For example, found that 7-year-old children only showed explicit ethnic prejudice when either a pro-prejudice norm and/or an out-group threat was made salient.…”
Section: Studymentioning
confidence: 99%
“…Only positive traits were included because developmental research indicates that children older than seven years are less willing to discriminate between social groups in terms of negative dimensions, whereas they will do so in terms of positive traits (e.g., Rutland et al 2007). All items were relatively normally distributed around the midpoint of the answer scale and the interitem correlations were below .90 with a few exceptions.…”
Section: Variablesmentioning
confidence: 99%
“…Among the different explanations offered for the PNAE, it is the normative account which has so far received most support (Amiot & Bourhis, 2003, 2005aRutland et al, 2007). The normative explanation assumes that certain discriminatory behaviours (e.g.…”
Section: Group Size and Trait Valence As Predictors Of Intergroup Biasmentioning
confidence: 99%
“…attributing less positive characteristics) are seen as less inappropriate (Gardham & Brown, 2001). However, it has been shown that while people may be aware of a generic or moral norm against intergroup discrimination, they may also in some salient intergroup contexts be affected by a specific ideological or social-conventional norm that legitimizes national intergroup bias (Amiot & Bourhis, 2003, 2005aRutland et al, 2007).…”
Section: Group Size and Trait Valence As Predictors Of Intergroup Biasmentioning
confidence: 99%